2002
DOI: 10.1002/ajmg.10557
|View full text |Cite
|
Sign up to set email alerts
|

Balanced X chromosome inactivation patterns in the Rett syndrome brain

Abstract: In Rett syndrome (RTT), an X-linked disorder essentially limited to females, neurological development goes awry. Causing this disarray in neuronal function is a mutated form of a protein known as methyl-CpG-binding protein 2 (MeCP2). Because the MECP2 gene is subject to X chromosome inactivation (XCI) in females, a number of studies have addressed whether the percentage of cells inactivating the normal vs. mutant chromosome in heterozygous females influences the phenotypic outcome of MECP2 mutations. Because m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 40 publications
3
48
2
1
Order By: Relevance
“…A few studies, employing small patient sample sizes, have shown random X inactivation in brain tissue. 22,23 This is in contrast with results using Mecp2 knockout mouse models, where an association between skewed X inactivation in brain cells and phenotypic severity was found. 24,25 The difference in reported frequencies of skewed X inactivation may partly be attributed to different definitions of the 'skewed' state (ranging from 465 to 485%) and different patient groups.…”
Section: Discussioncontrasting
confidence: 96%
“…A few studies, employing small patient sample sizes, have shown random X inactivation in brain tissue. 22,23 This is in contrast with results using Mecp2 knockout mouse models, where an association between skewed X inactivation in brain cells and phenotypic severity was found. 24,25 The difference in reported frequencies of skewed X inactivation may partly be attributed to different definitions of the 'skewed' state (ranging from 465 to 485%) and different patient groups.…”
Section: Discussioncontrasting
confidence: 96%
“…A num- ber of studies have addressed the contribution of XCI to the pathogenesis of MeCP2 mutations (38,39). It is suggested that XCI patterns may partly explain phenotypic variability in human RTT with MeCP2 mutations (38) and in mouse RTT models (39). Our findings indicate that this is not the full picture and that paternal X chromosome inactivation in the extraembryonic lineage also contributes to the deleterious consequences of MeCP2 mutations and, most likely, other X-linked gene mutations.…”
Section: Maternally Transmitted Mecp2_e2 Null Allele Results In Apoptcontrasting
confidence: 51%
“…A num- ber of studies have addressed the contribution of XCI to the pathogenesis of MeCP2 mutations (38,39). It is suggested that XCI patterns may partly explain phenotypic variability in human RTT with MeCP2 mutations (38) and in mouse RTT models (39).…”
Section: Maternally Transmitted Mecp2_e2 Null Allele Results In Apoptmentioning
confidence: 99%
“…Several reports agree on a balanced XCI of peripheral leukocytes DNA as well as DNA from the brains of deceased patients in the majority of RTT cases so that the theoretically plausible hypothesis that the XCI is one of the major phenotype influencing factors cannot be definitively confirmed on an experimental level [Anvret and Wahlstrom, 1994;Auranen et al, 2001;Hoffbuhr et al, 2001;Nielsen et al, 2001;Shahbazian et al, 2002]. Besides, almost all investigations of the XCI have been performed on DNA from peripheral tissues, mostly leukocytes.…”
Section: Clinical Relevancementioning
confidence: 96%